FAKTOR YANG MEMPENGARUHI KEPUASAN KERJA PADA PETUGAS KESEHATAN DI PUSKESMAS KOTA PALU - Andriani, Veby; Rahmayanti, Zulmi (Ensiklopedia of Journal, 2024)
Abstract: Job satisfaction is an employee's attitude towards work which is related to the work situation. High job satisfaction can increase job satisfaction so that it can achieve organizational goals. Satisfied employees will be more involved with their work. Factors that influence job satisfaction are work motivation, work environment, and imbalance. The aim of this research is to see the influence of work motivation, work environment, and imbalance on job satisfaction among health workers at the Health Center Palu City. This type of research is quantitative with an observational approach carried out in August 2024 at the Health Center Palu City. The population in this study consisted of health workers who worked at the Health Center Palu City, namely 516 respondents. Determination of the sample using multistage random sampling technique, sampling using random sampling. This research method uses the Multiple Linear Regression test. The results of the multiple linear regression statistical test on work motivation on job satisfaction have a significant influence (ρ <0.05 = 0.000). The work environment on job satisfaction has a significant influence (ρ<0.05 = 0.000). An imbalance in job satisfaction has a significant influence (ρ<0.05 = 0.000). The advice that can be given is that the Community Health Center should further increase the motivation given to officers by always paying attention to everything that health officers need in their work.Keywords: Job Satisfaction, Work Motivation, Work Environment, Rewards